1996
DOI: 10.1016/s1074-7613(00)80277-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Somatic Mutation in the Generation of the Protective Humoral Immune Response against Vesicular Stomatitis Virus

Abstract: During most clinically relevant infections with cytopathic viruses, neutralizing antibodies are generated early, i.e., within the first week of infection. As early as 4 days after immunization of mice with vesicular stomatitis virus (VSV), a cytopathic virus closely related to rabies virus, hybridomas could be isolated that secreted virus-neutralizing IgGs. Such antibodies were devoid of somatic mutations, showed high binding avidities (approximately 10(9) M-1), and used V gene fragments predominantly belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 0 publications
6
98
0
Order By: Relevance
“…Although the average affinity of neutralizing Abs does barely increase during the course of VSV infection, point mutations of the V regions of Ig do occur in the maturation of the Ab response against VSV. These point mutations often lead to an increase of the in vitro neutralizing activity up to 100-fold (62). The finding that mAbs isolated from TNFR1 Ϫ/Ϫ mice exhibited low to intermediate neutralizing activities despite rather high avidities is compatible with hypermutation being impaired in the absence of classical GC formation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the average affinity of neutralizing Abs does barely increase during the course of VSV infection, point mutations of the V regions of Ig do occur in the maturation of the Ab response against VSV. These point mutations often lead to an increase of the in vitro neutralizing activity up to 100-fold (62). The finding that mAbs isolated from TNFR1 Ϫ/Ϫ mice exhibited low to intermediate neutralizing activities despite rather high avidities is compatible with hypermutation being impaired in the absence of classical GC formation.…”
Section: Discussionmentioning
confidence: 97%
“…After VSV infection, the neutralizing activity of VSV-specific IgG mAbs can be used as an indicator for somatic mutation, because for some V H families the in vitro neutralizing activity of germline Abs may be 30 -100-fold lower than those of somatically mutated Abs (62). The increase in avidity for VSV binding between germline IgGs (that exhibit average avidities of 10 Ϫ8 to 10 Ϫ9 M Ϫ1 ) and somatically mutated IgGs was only about 2-5-fold (62). Therefore, the increase in avidity is probably not a good indicator for the maturation of the B cell response after VSV infection.…”
Section: Generation Of High Avidity Neutralizing Igg In the Spleen Ofmentioning
confidence: 98%
See 1 more Smart Citation
“…Restriction of Ig gene usages in antigen-specific B cells have been reported in both animal and human studies of antibody responses towards a variety of antigens, ranging from hapten, carbohydrate, viral protein, Rhesus D antigens, to other self proteins (Berek and Milstein, 1987;Casadevall and Scharff, 1991;Minnerath et al, 1995;Perera et al, 2000a;Perera et al, 2000b;Zhang et al, 2006), while others reported diverse antibody responses to confined regions of foreign proteins or homologs of self proteins (Andria et al, 1990;Caton et al, 1991;Kalinke et al, 1996). We previously showed that antibody gene usages of rotavirus (RV)-specific B cells differed from that of randomly selected B cells, with a distinct bias in the usage of gene segments in the V H 1 and V H 4 families.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the ability of Ung 2/2 mice to elicit isotype switching in vivo in a more physiologically relevant situation, we used VSV infection, a classical model for analyzing Ab responses to acute viral infection (33). Because SHM is not required for VSV neutralization (34,35), the accumulation of neutralizing IgG in the serum of infected mice over time is a good indicator for CSR ability in vivo that is not conditioned by the contribution of affinity maturation. VSV-infected Ung 2/2 mice showed dramatically impaired production of anti-VSV neutralizing IgG, as measured by their capacity to inhibit cell lysis in monolayers.…”
Section: Drastically Reduced Csr In Ung 2/2 Mice In Response To Vsv Imentioning
confidence: 99%